Cost-Utility Analysis Addition of Bevacizumab to Standard Chemotherapy in KRAS-mutation Colorectal Cancer - Putri, Devi Andiani; Setiawan, Didik; Yamsun, Muhammad (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2025)
There is a high incidence of colorectal cancer in Indonesia. Colorectal cancer was ranked fourth with an incidence of 8.6% and a colon cancer mortality rate of 4% while rectal cancer was 3.6% in Indonesia. The addition of Bevacizumab to Standard chemotherapy (FOLFOX/FOLFIRI/XELOX) in KRAS-mutation colorectal cancer patients has better clinical outcomes; however, it has a very high cost in terms of colorectal cancer treatment. The objective of this study was to determine the utility and economic impact of adding Bevacizumab as an adjunct therapy for KRAS-mutation colorectal cancer patients. A Markov model was developed to estimate the Cost-utility analysis (CUA) using a societal perspective. Humanistic outcomes are expressed in the form of QALY (Quality-adjusted life years) using an EQ-5D-5L instrument with an Indonesian value set. Medical expenses data were collected from both RSUP Dr. Sardjito and patients. Utility data were obtained from interviews with 30 patients undergoing chemotherapy at the hospital. This study compared the cost and utility of patients receiving Bevacizumab supplementation or patients receiving standard chemotherapy alone. The societal perspective resulted in a cost-effectiveness ratio (ICER) of US3.098 per QALY. The addition of Bevacizumab to standard chemotherapy in KRAS-mutation colorectal cancer patients is considerably cost-effective from a societal perspective.